Novel Meiotic miRNAs and Indications for a Role of PhasiRNAs in Meiosis - Dukowic-Schulze, Stefanie; Sundararajan, Anitha; Ramaraj, Thiruvarangan; Kianian, Shahryar; Pawlowski, Wojciech P.; Mudge, Joann; Chen, Changbin (Frontiers in Plant Science, 2016)
Small RNAs (sRNA) add additional layers to the regulation of gene expression, with siRNAs directing gene silencing at the DNA level by RdDM (RNA-directed DNA methylation), and miRNAs directing post-transcriptional regulation of specific target genes, mostly by mRNA cleavage. We used manually isolated male meiocytes from maize (Zea mays) to investigate sRNA and DNA methylation landscapes during zygotene, an early stage of meiosis during which steps of meiotic recombination and synapsis of paired homologous chromosomes take place. We discovered two novel miRNAs from meiocytes, and identified putative target genes. Furthermore, we detected abundant phasiRNAs of 21 nt and 24 nt length. PhasiRNAs are phased small RNAs which occur in 21 nt or 24 nt intervals, at a few hundred loci, specifically in male reproductive tissues in grasses. So far, the function of phasiRNAs remained elusive. Data from isolated meiocytes now revealed elevated DNA methylation at phasiRNA loci, especially in the CHH context, suggesting a role for phasiRNAs in cis DNA methylation. In addition, we consider a role of these phasiRNAs in chromatin remodeling/ dynamics during meiosis. However, this is not well supported yet and will need more additional data. Here, we only lay out the idea due to other relevant literature and our additional observation of a peculiar GC content pattern at phasiRNA loci. Chromatin remodeling is also indicated by the discovery that histone genes were enriched for sRNA of 22 nt length. Taken together, we gained clues that lead us to hypothesize sRNA-driven DNA methylation and possibly chromatin remodeling during male meiosis in the monocot maize which is in line with and extends previous knowledge.